Identification, Prevalence, and Infestation Patterns of Ectoparasitic In MP Hybrid Type Culled Laying Ducks In Gedang Sub Village, Modopuro Village, Mojosari Sub District, Mojokerto District - Aurandini, Nailla Ridhani; Hastutiek , Poedji; Utama , Suzanita; Sunarso, Agus; Suprihati , Endang; Witaningrum, Adiana Mutamsari (Journal of Parasite Science, 2024)
The purpose of this study was to identify ectoparasites and to determine the prevalence and infestation patterns of ectoparasites that attack the MP hybrid type culled ducks in Gedang Hamlet, Modopuro Village, Mojosari District, Mojokerto Regency. This study used a sample of 100 culled laying ducks of the MP hybrid type. The obtained ectoparasites were identified at the labaroratory of division parasitology, Faculty of veterinary medicine, Universitas Airlangga, Surabaya, using the permanent mounting method without staining and viewed using a microscope with 40-100x magnification. This study found 71 samples positively infested with ectoparasites out of 100 samples of culled MP hybrid ducks examined with (prevalence of 71%). The types of ectoparasites found in this study were Menacanthus stramineus (25%), Menopon gallinae (9%), and Anaticola crassicornis (59%). Correspondence analysis test was conducted to show the pattern of infestation of the ectoparasites. The head-neck region was infested by M. stramineus and M. gallinae, while the back, wings, abdomen and tail regions were infested by A. crassicornis. A. crassicornis mostly attacked the MP hybrid type of culled laying ducks on the wings, compared to the back, abdomen and tail. A. crassicornis is an ectoparasite that is typical for the wing region, while M. gallinae and M. stramineus are ectoparasites that are typical for the head-neck region.